2023
DOI: 10.3389/fvets.2023.986382
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the gut microbiome and resistome in captive African and Asian elephants on the same diet

Abstract: Elephants are endangered species and threatened with extinction. They are monogastric herbivorous, hindgut fermenters and their digestive strategy requires them to consume large amounts of low quality forage. The gut microbiome is important to their metabolism, immune regulation, and ecological adaptation. Our study investigated the structure and function of the gut microbiota as well as the antibiotic resistance genes (ARGs) in captive African and Asian elephants on the same diet. Results showed that captive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Leveraging amplicon sequencing data, PICRUSt2 analysis was employed for predictive and analytical functional profiling of microbial communities(C. Yang et al, 2023). Employing Wilcoxon rank-sum tests and Metastats analysis, a significance threshold of p-value <0.05 was used for differential significance screening, with the Bonferroni correction applied to the p-values to minimize the potential for false positives (Feng et al, 2023;Neuhäuser, 2015). This methodology was adopted to assess whether significant interspecies diversity exists among groups.…”
Section: Analysis Of 16s Rrna Gene Sequences and Bioinformaticsmentioning
confidence: 99%
“…Leveraging amplicon sequencing data, PICRUSt2 analysis was employed for predictive and analytical functional profiling of microbial communities(C. Yang et al, 2023). Employing Wilcoxon rank-sum tests and Metastats analysis, a significance threshold of p-value <0.05 was used for differential significance screening, with the Bonferroni correction applied to the p-values to minimize the potential for false positives (Feng et al, 2023;Neuhäuser, 2015). This methodology was adopted to assess whether significant interspecies diversity exists among groups.…”
Section: Analysis Of 16s Rrna Gene Sequences and Bioinformaticsmentioning
confidence: 99%
“…Research has demonstrated that animal immune, digestive and reproductive health are intrinsically linked to the composition and the corresponding functional processes of the hostassociated microbial communities 11 . In the context of elephant microbiome research, focus has been placed on the characterisation of African and Asian elephant intestinal microbiota in an effort to improve the health status and welfare of these animals [12][13][14][15][16][17][18][19] , restore the microbial diversity of captive elephants 12,14,15,17,19,20 , and enhance their diet 13,16,20 . Investigation into the respiratory microbiota of this species may enable broad characterisation of the microbiota of healthy animals, documentation of undescribed microbial diversity, and identi cation of relationships between microbiota and host disease phenotypes.…”
Section: Introductionmentioning
confidence: 99%